The implementation of Shariah compliant human milk bank for premature infants in Malaysia - Daud, Normadiah; Ali, Zurina; Ismail, Hamizah; Jamani, Nurjasmine Aida; Mohd Arifin, Siti Roshaidai; Syed Abd Hamid, Syed Abdul Khaliq (Innovare Academics Sciences Pvt. Ltd, 2020)
Human milk is the perfect food for human infants. The World Health Organisation (WHO) recommends exclusive breastfeeding for 6 months and continuation of breastfeeding for 2 years and beyond after the introduction of complementary food. Full exclusive breastfeeding provides almost all of the nutrition required by healthy full-term infants and also protection against illness. In Islam, it is the right of every infant to receive the best source of nutrition for their development, a feature that can be found in mother’s milk. However, some mothers are unable to breastfeed their infants due to various unavoidable reasons. In Malaysia, cases such as premature birth, babies born from HIV positive mothers, multiple births are becoming more prevalent. Research evidence shows that infant receiving breastmilk in the early days have low risk of developing critical illness. This creates a need for the establishment of the human milk bank in Malaysia. Unfortunately, there are hurdles in setting up a human milk bank in Malaysia. This is because the 97th Conference of the Fatwa Committee National Council for Islamic Religious Affair of Malaysia held on 15th – 17th December 2011 forbids the establishment of a human milk bank. Thus, the authors propose that a Shariah-compliant Human Milk Bank to be established.